The Challenges of collaboration and democratic participation in turbulent and unsettled times - Watson, Sophie (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2018)
This paper proposes new key ways to thinking about self-organisation in cities in what, I suggest, are increasingly unsettled and turbulent times. The importance of thinking about self-organisation in cities is all the more salient in the current economic and social context where in many parts of the world there is a withdrawal by the state from public involvement and expenditure, which is impacting on urban citizens, particularly those who are vulnerable, in increasing negative ways. Self-organisation is thus an important and key direction for the future, if cities are to remain inclusive, just and responsive to local needs. Yet such self-organisation can only be truly meaningful and effective if it is conducted collaboratively and democratically, involving as many people as possible, particularly those whose voices are not often heard. In so doing, it is also important to recognise that such involvement and democratic participation is not always consensual; rather conflict is inevitable and potentially positive, as people learnt to recognises their differences which are often implicated in power, and to negotiate solutions together.